2022
DOI: 10.3390/su15010325
|View full text |Cite
|
Sign up to set email alerts
|

Small-Town Citizens’ Technology Acceptance of Smart and Sustainable City Development

Abstract: Citizens are an essential part of the process of smartification and sustainable development of cities as they must adopt, understand and interact with the enabling technologies of digital transformation of societies, cities, and public administration. Therefore, technology acceptance is crucial to creating smart and citizen-centered cities. This is even more challenging in small towns that suffer from an aging population, desertification, lack of infrastructure, and especially the digital divide. The purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 120 publications
0
17
0
Order By: Relevance
“…The findings indicated that several factors significantly extended the TAM, among the most frequent factors were social media, perceived enjoyment, subjective norm, self-efficacy, perceived critical mass, perceived connectedness, perceived security, and perceived trust. In the same vein, in this other study [26], the digital gap that might exist across different generations was delved into and it was uncovered that age plays a significant role in influencing the optimism, innovativeness, and perceived usefulness concerning the adoption of social media. Finally, study [42] constructed a comprehensive model to investigate the influence of social-media-use factors on electronic banking adoption.…”
mentioning
confidence: 84%
“…The findings indicated that several factors significantly extended the TAM, among the most frequent factors were social media, perceived enjoyment, subjective norm, self-efficacy, perceived critical mass, perceived connectedness, perceived security, and perceived trust. In the same vein, in this other study [26], the digital gap that might exist across different generations was delved into and it was uncovered that age plays a significant role in influencing the optimism, innovativeness, and perceived usefulness concerning the adoption of social media. Finally, study [42] constructed a comprehensive model to investigate the influence of social-media-use factors on electronic banking adoption.…”
mentioning
confidence: 84%
“…A review of the relevant literature informed this multi-lens approach, drawing from theoretical considerations, case studies of small cities, and official government documents. This research method focused on five critical themes drawn from the literature as having a substantial impact on the sustainability of small cities in Saudi Arabia: (i) existing infrastructure [8, [13][14][15][16][17][18][19]; (ii) urban governance and administration procedures [36][37][38]; (iii) relationships with other cities [47][48][49][50][51][52][53][54][55][56]; (iv) current economic activity [18,23,[25][26][27][28][29][30][31][32][33][34][35]; and (v) potential development opportunities [57][58][59][64][65][66]. By exploring these five components in unison, it was possible to gain a more comprehensive and accurate understanding of the current experts' perception of small cities in Saudi Arabia, while considering the contributing factors which may shape their future growth.…”
Section: Methodsmentioning
confidence: 99%
“…An urban system is fundamentally a regional unit consisting of locations influenced by social, economic, and functional bonds that are connected hierarchically [51]. The advancement in communication technologies hastens these changes, strengthens the interactions between cities within the region, and amplifies their scope [52,53]. Consequently, it is imperative to approach cities as an amalgamation of urban settlements as opposed to separated entities independent of other localities in their region.…”
Section: Relationships and Interconnections Between Small Cities And ...mentioning
confidence: 99%
“…A clear description and assessment of citizens' roles in smart cities might assist us in properly managing technology. In fact, smart cities frequently fail to fulfill their objectives because people (the end users) are not involved in their creation or are unable to use the technology for a plethora of factors [38]. Among other things, they are an excellent factor in assessing the service quality [39,40].…”
Section: Literature Reviewmentioning
confidence: 99%